Wilfred Thesiger the life of the great explorer - Maitland, Alexander (Overlook Press, 2011)
Wilfred Thesiger (1910-2003), the last of the great gentlemen explorer-adventurers, journeyed for sixty years to some of the remotest, most dangerous places on earth from the mountains of western Asia to the marshes of Iraq. The author of Arabian Sands, The Marsh Arabs and The Life of my Choice, he was a legend in his own lifetime but his character and motivations have remained an intriguing enigma.